Time-resolved grazing-incidence X-ray diffraction measurement to understand the effect of hydrogen on surface strain development in super duplex stainless steel. (October 2020) - Örnek, Cem; Larsson, Alfred; Harlow, Gary S; Zhang, Fan; Kroll, Robin; Carlà, Franceso; Hussain, Hadeel; Kivisäkk, Ulf; Engelberg, Dirk L; Lundgren, Edvin; Pan, Jinshan
Abstract: Grazing-incidence x-ray diffraction was employed to measure, operando, during electrochemical hydrogen charging, the lattice strain development of the near-surface in super duplex stainless steel under applied tensile load. Hydrogen absorption led to the formation of tensile strains in both the austenite (γ) and ferrite (δ) phases perpendicular to the loading axis, whereas compressive strains were formed in the ferrite phase parallel to the loading direction, despite the acting tensile load. The earliest stages of degradation are discussed in light of understanding hydrogen embrittlement. Graphical abstract: Image, graphical abstract